ANALISIS DAMPAK EKONOMI PANDEMI COVID-19 TERHADAP PENGRAJIN BATIK DI KECAMATAN KEREK TUBAN - Laila Murningsih Novrian Wakhidah; Muhammad Faisal Abdullah; Hendra Kusuma (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to see the difference in the economic impact of the condition of the batik craftsmen of Gedog during the Covid-19 pandemic compared to before the Covid-19 in Kerek District, Tuban Regency. The object of this research is the craftsmen of Gedog written batik in Kerek District, with a total of 54 craftsmen. The type of data collected is primary data with a closed questionnaire data collection technique. Data analysis methods include descriptive statistical test, normality test and Wilcoxom test. The results of this study indicate that t there is a difference during the Covid-19 pandemic compared to before the Covid-19 Gedog written batik craftsmen in Kerek District, Tuban Regency. The positive impact of the increase in time before the Covid-19 in Gedog written batik is that the community has achieved independence in improving their economy through new skills in making Gedog batik so that they get a bigger income than before. On the negative side, when there was Covid-19, people felt tired due to a lack of production and marketing due to large-scale restrictions which resulted in reduced income and public interest.